Alternate RASSF1 Transcripts Control SRC Activity, E-Cadherin Contacts, and YAP-Mediated Invasion - Vlahov, Nikola; Scrace, Simon; Soto, Manuel Sarmiento; Grawenda, Anna M.; Bradley, Leanne; Pankova, Daniela; Papaspyropoulos, Angelos; Yee, Karen S.; Buffa, Francesca; Goding, Colin R.; Timpson, Paul; Sibson, Nicola; et al. (Current biology, 2015)
Tumor progression to invasive carcinoma is associated with activation of SRC family kinase (SRC, YES, FYN) activity and loss of cellular cohesion. The hippo pathway-regulated cofactor YAP1 supports the tumorigenicity of RAS mutations but requires both inactivation of hippo signaling and YES-mediated phosphorylation of YAP1 for oncogenic activity. Exactly how SRC kinases are activated and hippo signaling is lost in sporadic human malignancies remains unknown. Here, we provide evidence that hippo-mediated inhibition of YAP1 is lost upon promoter methylation of the RAS effector and hippo kinase scaffold RASSF1A. We find that RASSF1A promoter methylation reduces YAP phospho-S127, which derepresses YAP1, and actively supports YAP1 activation by switching RASSF1 transcription to the independently transcribed RASSF1C isoform that promotes Tyr kinase activity. Using affinity proteomics, proximity ligation, and real-time molecular visualization, we find that RASSF1C targets SRC/YES to epithelial cell-cell junctions and promotes tyrosine phosphorylation of E-cadherin, β-catenin, and YAP1. RASSF1A restricts SRC activity, preventing motility, invasion, and tumorigenesis in vitro and in vivo, with epigenetic inactivation correlating with increased inhibitory pY527-SRC in breast tumors. These data imply that distinct RASSF1 isoforms have opposing functions, which provide a biomarker for YAP1 activation and explain correlations of RASSF1 methylation with advanced invasive disease in humans. The ablation of epithelial integrity together with subsequent YAP1 nuclear localization allows transcriptional activation of β-catenin/TBX-YAP/TEAD target genes, including Myc, and an invasive phenotype. These findings define gene transcript switching as a tumor suppressor mechanism under epigenetic control. [Display omitted] •Methylation of RASSF1A correlates with loss of hippo-inhibitory phospho-S127-YAP1•SRC, FYN, and YES are activated by RASSF1C in RASSF1A-methylated cells•RASSF1C promotes E-cadherin internalization and reduces cell junction integrity•RASSF1A loss drives RASSF1C-YAP1/β-catenin-mediated transcription and invasion In a wide variety of sporadic malignancies, promoter methylation of the RASSF1 gene is associated with tumor invasion and metastasis. Vlahov et al. show that the clinical phenotype is driven by both RASSF1A loss and the independently transcribed RASSF1C isoform, which promotes SRC activation, pseudo-EMT, and β-catenin/YAP1-dependent invasion of tumor cells.